2017
DOI: 10.1017/s0885715617000458
|View full text |Cite
|
Sign up to set email alerts
|

XRD study of phase transformations in lithiated graphite anodes by Rietveld method

Abstract: Commercial anodes with different state of charge are investigated by X-ray diffraction technique using Rietveld method for data collected with standard laboratory equipment. It is shown that full profile refinement gives good approximation for quantitative description of the charge/discharge process and may be used for estimation of real state of charge (SoC). Careful analysis of the diffraction profile with Rietveld method allows us to quantitatively distinguish the contribution of different LixC6 phases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 24 publications
9
58
0
Order By: Relevance
“…The similarity between the stages observed during Gr lithiation and delithiation is consistent with the well‐known reversible nature of Li + ion intercalation into Gr . As lithiation progresses the sequential formation of dilute stage I (denoted I'), stage IV/III, stage IIL, stage II, and stage I has been reported . Of these stages, the stoichiometry of stages II and I has been determined as LiC 12 and LiC 6 ; ambiguity exists as to the exact stoichiometry of the other three stages.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…The similarity between the stages observed during Gr lithiation and delithiation is consistent with the well‐known reversible nature of Li + ion intercalation into Gr . As lithiation progresses the sequential formation of dilute stage I (denoted I'), stage IV/III, stage IIL, stage II, and stage I has been reported . Of these stages, the stoichiometry of stages II and I has been determined as LiC 12 and LiC 6 ; ambiguity exists as to the exact stoichiometry of the other three stages.…”
supporting
confidence: 71%
“…The spectra were collected in the 0.8–5 Å d ‐spacing range. However, given that the strongest Bragg peaks belonging to the (00l) family of planes of Li–Gr intercalates occur between 3.2 and 3.8 Å, only this range is shown. No peaks were observed from crystalline phases of Si.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the space group of the intermediate phases, there seems to be an agreement in the literature that LiC 12 crystallizes in P6/mmm with AAAA-type stacking (Imai & Watanabe, 2007;Woo et al, 1983;Guerard & Herold, 1975;Billaud et al, 1996). The diluted stage II compound LiC 18 is reported to have a stacking sequence of AABB (Woo et al, 1983;Billaud et al, 1996), with the suggested space group P6 3 mc (Missyul et al, 2017). As for the stage III compound, the stacking sequence was suggested to be AABAACAA or AABAABAA (Billaud et al, 1996;Billaud & Henry, 2002).…”
Section: Introductionmentioning
confidence: 53%
“…Through literature review, five main stages are identified and deconvoluted from the spectra collected using their reported d-spacing ranges: dilute stage I (denoted I 0 ), stage IV/III, stage IIL, stage II, and stage I. [26][27][28][29] The following equation is used to estimate the average lithium content x of each layer (expressed in Li atoms per C 6 ):…”
Section: Energy Dispersive X-ray Diffraction (Edxrd)mentioning
confidence: 99%